Psychosocial Assessment of Candidates for Transplantation (PACT) Score Identifies High Risk Patients in Pediatric Renal Transplantation - Freischlag, Kyle W.; Chen, Vivian; Nagaraj, Shashi K.; Chua, Annabelle N.; Chen, Dongfeng; Wigfall, Delbert R.; Foreman, John W.; Gbadegesin, Rasheed; Vikraman, Deepak; Chambers, Eileen T. (Frontiers in Pediatrics, 2019)
Background: Currently, there is no standardized approach for determining psychosocial readiness in pediatric transplantation. We examined the utility of the Psychosocial Assessment of Candidates for Transplantation (PACT) to identify pediatric kidney transplant recipients at risk for adverse clinical outcomes. Methods: Kidney transplant patients <21-years-old transplanted at Duke University Medical Center between 2005 and 2015 underwent psychosocial assessment by a social worker with either PACT or unstructured interview, which were used to determine transplant candidacy. PACT assessed candidates on a scale of 0 (poor candidate) to 4 (excellent candidate) in areas of social support, psychological health, lifestyle factors, and understanding. Demographics and clinical outcomes were analyzed by presence or absence of PACT and further characterized by high (≥3) and low (≤2) scores. Results: Of 54 pediatric patients, 25 (46.3%) patients underwent pre-transplant evaluation utilizing PACT, while 29 (53.7%) were not evaluated with PACT. Patients assessed with PACT had a significantly lower percentage of acute rejection (16.0 vs. 55.2%, p = 0.007). After adjusting for HLA mismatch, a pre-transplant PACT score was persistently associated with lower odds of acute rejection (Odds Ratio 0.119, 95% Confidence Interval 0.027–0.52, p = 0.005). In PACT subsection analysis, the lack of family availability (OR 0.08, 95% CI 0.01–0.97, p = 0.047) and risk for psychopathology (OR 0.34, 95% CI 0.13–0.87, p = 0.025) were associated with a low PACT score and post-transplant non-adherence. Conclusions: Our study highlights the importance of standardized psychosocial assessments and the potential use of PACT in risk stratifying pre-transplant candidates.